Anorexia nervosa during pregnancy. - Goldman, Ran D. (2003)
QUESTION: A 22-year-old patient in my clinic was diagnosed with anorexia nervosa (AN) 7 years ago. She is now married and planning her first pregnancy. She is still underweight. What should she expect during pregnancy, and are there any implications for her unborn baby? ANSWER: Women with AN are at higher risk of complications during pregnancy, mainly because of low body weight. Apgar scores and birth weights of infants born to mothers with AN have been found to be significantly lower than those of infants born to healthy women. Rates of cesarean delivery, postnatal complications, and postpartum depression are higher among mothers with AN. Complications include hypothermia, hypoglycemia, infections, and increased rates of perinatal death. It is important to ensure appropriate intake of not only calories and proteins but also micronutrients, such as folic acid, to prevent neural tube defects.